THE PENAMBAHAN TERAPI LATIHAN MC.KENZIE PADA INTERVENSI SHORT WAVE DIATHERMY (SWD), TRANSCUTANEUS ELECTRICAL NERVE STIMULATION (TENS) DAN MASSAGE DAPAT LEBIH MENURUNKAN NYERI PINGGANG PADA KASUS LOW BACK PAIN - Kurniasih, Endah (Majalah Ilmiah Fisioterapi Indonesia; Vol 1 No 2 (2013): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2013.v01.i02.p07, 2013)
This research aimed to identifi addition intervention in Mc. Kenzie exercise, short wave diathermi, transcutaneous electrical nerve stimulation and massage reduce back pain in low back pain problem . Method : This research is using pre test and post test control group design. Patients were randomised into two groups : the Control Group (CG) that use SWD, TENS, and massage is 10 patients. The Experimental Group (EG) that SWD, TENS, massage and Mc.Kenzie exercise is 10 patients too. Result : The result of CG test which using compare means with paired sample t-test, p<0,05 (p=0,000) that mean the intervention in CG is having significant to reduce pain. In the result of EG test which using compare means with paired sample t-test, p<0,05 (p=0,000) that mean the intervention in EG is having significant to reduce pain. The result test researcher using compare mean test with Independent sample t-test, p<0,05 (p=0,003), that means there are significant different between EG result and CG result. In one tail hypothesis got result p<0,05, so it shows that intervention in EG more effective significantly than CG in to reduce low back pain . Conclusion : Addition intervention in Mc. Kenzie exercise, short wave diathermi, transcutaneous electrical nerve stimulation and massage reduce back pain in low back pain problem.
Keywords: low back pain, reduce pain, Mc.Kenzie exercise.